Functionalized Selenium Nanoparticles Synergizes With Metformin to Treat Breast Cancer Cells Through Regulation of Selenoproteins - Yang, Yu; Zhang, Zehang; Chen, Qi; You, Yuanyuan; Li, Xiaoling; Chen, Tianfeng (Frontiers in Bioengineering and Biotechnology, 2021)
Owing to high blood sugar levels and chronic inflammation, diabetes tends to cause the body to produce large amounts of free radicals, which damage tissue cells, reduce autoimmunity, and greatly increase the incidence of tumors. Selenium nanoparticles (SeNPs) show high antioxidant activity and an anti-tumor effect. Metformin is a clinical drug commonly used for the treatment of stage II diabetes. Therefore, in this study, different functionalized SeNPs combined with metformin were used for tumor cell treatment. The combination of Tween 80 (TW80)-SeNPs and metformin was found to have a synergistic effect on MCF-7 cells. The mechanism of this synergistic effect seemed to involve induction of DNA damage by affecting the generation of radical oxygen species through selenoproteins; upregulation of DNA-damage-related proteins including p-ATM, p-ATR, and p38; promotion of p21 expression; and downregulation of cyclin-dependent kinases and cyclin-related proteins，causing cell cycle arrest. In addition, the expression of AMPK was affected, which in turn affected the mitochondrial membrane potential to achieve the synergistic treatment effect.